2013
DOI: 10.1088/1748-9326/8/2/025020
|View full text |Cite
|
Sign up to set email alerts
|

The prospects for urban densification: a place-based study

Abstract: Study of the environmental outcomes of urban densification is a highly context-dependent task. Our study shows that collecting and processing place-based survey data by means of the softGIS method is clearly helpful here. With the map-based internet questionnaire each response remains connected to both the physical environment and the everyday life of the respondent. In our study of the Kuninkaankolmio area (located in the Helsinki metropolitan region) the survey data were combined with urban density variables… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 43 publications
0
27
1
1
Order By: Relevance
“…Geo-questionnaires and similar PPGIS methods have been applied to elicit public preferences on various subjects and at various spatial scales in a number of countries including Finland (Kahila, Kyttä 2009, Schmidt-Thomé et al 2013, Kahila-Tani et al 2015), Sweden (babelon et al 2016, Iceland (Pánek, benediktsson 2017), Czech Republic (Pánek et al 2017), USA (Alessa et al 2008, brown, Reed 2009, Schmidt-Thomé et al 2014, New Zealand (brown, weber 2012), Portugal and brazil (bugs, Kyttä 2016), and Australia (brown 2012a). A more comprehensive review of PPGIS data collection cases in academic research can be found in Brown and Kyttä (2014).…”
Section: Application Examplesmentioning
confidence: 99%
“…Geo-questionnaires and similar PPGIS methods have been applied to elicit public preferences on various subjects and at various spatial scales in a number of countries including Finland (Kahila, Kyttä 2009, Schmidt-Thomé et al 2013, Kahila-Tani et al 2015), Sweden (babelon et al 2016, Iceland (Pánek, benediktsson 2017), Czech Republic (Pánek et al 2017), USA (Alessa et al 2008, brown, Reed 2009, Schmidt-Thomé et al 2014, New Zealand (brown, weber 2012), Portugal and brazil (bugs, Kyttä 2016), and Australia (brown 2012a). A more comprehensive review of PPGIS data collection cases in academic research can be found in Brown and Kyttä (2014).…”
Section: Application Examplesmentioning
confidence: 99%
“…Nevertheless, as the questionnaire did not address the reasons to move to a location, the possibility of bi-directional causation cannot be ruled out completely. Living in certain locations for a long time may influence peoples' preferences for housing choice (Schmidt-Thomé et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…This method was an example of a web-based Public Participation GIS (PPGIS) tool that has been utilised in several Finnish cities as well as in Japan and Australia (e.g., Kyttä, Broberg, Tzoulas, & Snabb, 2013;Schmidt-Thomé, Haybatollahi, Kyttä, & Korpi, 2013). We sought the information concerning the residential and mobility prospects in four survey sections.…”
Section: Methodsmentioning
confidence: 99%
“…The research reported herein follows the Web‐based approach to PPGIS and focuses on a particular method of soliciting and collecting public input on land use and development preferences. The method is called geo‐questionnaire and its roots are in the work of Kyttä and colleagues who have used it in the context of urban planning and environmental psychology as part of the softGIS methodology (Kahila and Kyttä , Kyttä et al , Schmidt‐Thomé et al ). Geo‐questionnaire belongs to the category of Computer‐Assisted Web Interviewing (CAWI) methods aimed at collecting qualitative and quantitative data from a broad group of respondents.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies used various techniques of expressing development preferences. In a study by Schmidt‐Thomé et al () preferences and interests toward housing developments were elicited through the selection of pre‐defined geographic objects visible on a map and by linking them with attribute information. Studies have also used features drawn by participants to spatially denote preferences on a map.…”
Section: Introductionmentioning
confidence: 99%